Evaluation of the impact of anthropogenic activities on arsenic, cadmium, chromium, mercury, lead, and polycyclic aromatic hydrocarbon levels in seafood from the Gulf of Naples, Italy. Issue 9 (29th July 2018) - Fasano, E.; Arnese, A.; Esposito, F.; Albano, L.; Masucci, A.; Capelli, C.; Cirillo, T.; Nardone, A.
ABSTRACT: The principal aim of this study was to monitor the occurrence of some metals and polycyclic aromatic hydrocarbons (PAHs) in fish and mussels from the Gulf of Naples. A comparison with previous researches of the same area was carried out, and the intakes of these compounds through the diet and their effect on the tolerable intake values (when available) were assessed. Cadmium (Cd), chromium (Cr), and lead (Pb) were detected by flameless atomic absorption spectroscopy (Cd, Cr, and Pb); arsenic (As) and mercury (Hg) were detected by applying the hydride method. PAHs were detected by high-performance liquid chromatography. Widespread contamination was found. Among the metals, Hg showed the highest maximum levels of 284.94 ng/g wet weight (ww) in fish and 480.00 ng/g ww in mussels. Chrysene, phenanthrene, fluoranthene, anthracene, and benzo[k]fluoranthene were the most common PAHs in fish, whereas benzo[a]anthracene, pyrene, phenanthrene, acenaphthylene, and acenaphthene were the most frequently occurring compounds in mussels. The concentrations of As, Cr, Hg, Pb, and PAHs in fish were found to decrease over a period of 30 years, whereas the Cd levels remained constant. The Hg, Pb, and PAH levels in mussels increased over the period 2010 to 2016. Finally, the average consumption of mussels led to the highest effect on the Tolerable Daily Intake of Hg, which was exceeded by 19%.